Public awareness of climate risks and opportunities in Scotland - Millar, Catriona; Mulholland, Ciaran; Corner, Adam (Ipsos, 2022)
This study explores the Scottish public’s understanding of current and future risks and opportunities posed by a changing climate. Having a better understanding of the public’s awareness of the risks of climate change will help provide a platform for more effective engagement at the community and society level. Echoing recent trends, concern about climate change in Scotland was high and increasing, and a majority felt that Scotland was already feeling the effects of climate change. When asked what the specific impacts on Scotland were likely to be, respondents tended to focus on weather-related impacts, and extreme weather was generally seen as becoming more common in Scotland. Weather-related events were, however, generally seen as more of a serious problem for Scotland overall than for respondents’ local areas.
Keywords: Climate Change; climate change adaptation; climate change impacts; public awareness; public engagement